2013
DOI: 10.1371/journal.pone.0063857
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking Pten in Osteoblasts Have Improved Intramembranous and Late Endochondral Fracture Healing

Abstract: The failure of an osseous fracture to heal (development of a non-union) is a common and debilitating clinical problem. Mice lacking the tumor suppressor Pten in osteoblasts have dramatic and progressive increases in bone volume and density throughout life. Since fracture healing is a recapitulation of bone development, we investigated the process of fracture healing in mice lacking Pten in osteoblasts (Ocn-cretg/+;Ptenflox/flox). Mid-diaphyseal femoral fractures induced in wild-type and Ocn-cretg/+;Ptenflox/fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 36 publications
(54 reference statements)
3
29
1
Order By: Relevance
“…Studies on Phosphatase and tensin homolog (PTEN), a negative regulator of PI3K, revealed that PTEN deletion in osteoprogenitors resulted in their increased proliferation [10] and late stage osteoblast-specific PTEN deletion led to increased bone mineral density [11]. In agreement with these findings, mice lacking PTEN in osteoblasts have improved fracture healing [12]. …”
Section: Introductionmentioning
confidence: 98%
“…Studies on Phosphatase and tensin homolog (PTEN), a negative regulator of PI3K, revealed that PTEN deletion in osteoprogenitors resulted in their increased proliferation [10] and late stage osteoblast-specific PTEN deletion led to increased bone mineral density [11]. In agreement with these findings, mice lacking PTEN in osteoblasts have improved fracture healing [12]. …”
Section: Introductionmentioning
confidence: 98%
“…All statistical analyses were conducted with the software R 2.15 (R Foundation for Statistical Computing, Vienna, Austria). Sex was not investigated in the present study as Burgers and co-workers (2013) found sex to be insignificant for K , F max , and healing rate.…”
Section: Methodsmentioning
confidence: 82%
“…The previous study, approved by the Institutional Animal Use and Care Committee at the Van Andel Research Institute, Grand Rapids, MI, used 96 mice to investigate the influence of Pten on biomechanical properties of the femur during fracture healing (Burgers et al, 2013). Of these mice, the 66 subjected to mechanical testing and micro-computed tomography (μ-CT) imaging were the focus of the present study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations